1999
DOI: 10.1016/s0002-9440(10)65167-x
|View full text |Cite
|
Sign up to set email alerts
|

The New Apolipoprotein A-I Variant Leu174 → Ser Causes Hereditary Cardiac Amyloidosis, and the Amyloid Fibrils Are Constituted by the 93-Residue N-Terminal Polypeptide

Abstract: We identified a novel missense mutation in the apolipoprotein A-I gene, T2069C Leu(174) --> Ser, in a patient affected by familial systemic nonneuropathic amyloidosis. The amyloid deposits mostly affected the heart of the proband, who underwent transplantation for end-stage congestive heart failure. Amyloid fibrils of myocardial and periumbilical fat samples immunoreacted exclusively with anti-ApoA-I antibodies. Amyloid fibrils extracted from the heart were constituted, according to amino acid sequencing and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
74
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 19 publications
(18 reference statements)
6
74
0
2
Order By: Relevance
“…These data strengthen and expand previous descriptions of single patients in whom testicular failure was reported in the medical history several years before a diagnosis of cardiac 9 or visceral 11,12 apoA-I amyloidosis was made.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data strengthen and expand previous descriptions of single patients in whom testicular failure was reported in the medical history several years before a diagnosis of cardiac 9 or visceral 11,12 apoA-I amyloidosis was made.…”
Section: Discussionsupporting
confidence: 88%
“…8 Similarly testicular biopsy showed amyloid deposits several years before the occurrence of severe amyloid cardiomyopathy in a patient carrying the leucine 174 serine mutation of apoA-I. 9 ApoA-I, the major component of high density lipoproteins, can cause systemic amyloidosis at the presence of specific amino acid replacements. A total of 12 amyloidogenic apoA-I variants have been identified to date.…”
mentioning
confidence: 99%
“…35 Although the precise mechanism for the amyloidogenicity of variant apoAI remains unclear, it has been shown that mutated apoAI undergoes proteolytic cleavage releasing the amyloidogenic N-terminal fragment from the fulllength protein. 5,7,9 There are now 19 mutations in the APOAI gene known to be association with hereditary systemic apoAI amyloidosis, including the four novel amyloidogenic variants described here ( Table 1). The phenotype of apoAI amyloidosis may be fairly aggressive and present in teenagers with CKD, hepatomegaly, cardiomyopathy, and sometimes neuropathy 19,44 or may be extremely indolent and clinically insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of apoAI amyloidosis may be fairly aggressive and present in teenagers with CKD, hepatomegaly, cardiomyopathy, and sometimes neuropathy 19,44 or may be extremely indolent and clinically insignificant. Interestingly, most C-terminal variants seem to be associated with hoarseness due to laryngeal amyloid deposits (Table 1), 7,9,10,20,40 although there is even substantial heterogeneity in the age at onset and clinical manifestations between patients with identical mutations. G26R, which is the most frequently reported amyloidogenic apoAI variant among Northern Europeans, is associated with amyloid de- apart from that in an Italian family with laryngeal, cardiac, and skin amyloidosis who carried the Leu90Pro apoAI variant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation